Determinants and perceptions of social mobility in Poland, 1992-2008 - Katarzyna Sokołowska (Contemporary Economics, 2014)
The purpose of this article is to analyse the factors affecting social mobility in Poland, based on results obtained from the estimation of logit models for the years 1992 - 2008 as well as from interviews asking about the necessary conditions to achieve success in life. Data used in this work come from the Polish General Social Survey carried out by the Institute of Social Studies of the University of Warsaw on a representative sample of adult household members. This set contains interviews conducted in the years 1992 - 2008 and includes 16,234 respondents. Studies using logit models to answer the question posed in the present study show that the probability of success in life in Poland is determined by both ability and level of education; interview responses to the same question, however, show that family origins, parents# level of education and connections are just as important. Most interestingly, the percentage of people indicating the importance of these factors was higher in 2002 than it was in 1992.
Keywords: C25; J62; 330; intergenerational mobility; life success factors; logit model